Bilen virker: Forestillinger om Tyskland i Norge - Skåden, Kristina (Tidsskrift for kulturforskning, 2006)
How does material culture act in the relation between nations? This is the main question in this article. The author wishes to uncover the changed roles the "Volkswagen" has had during it’s time, both in the sense of symbol and by its materiality. Further the article describes what the "Volkswagen" has done for the relations between Norway and Germany. Inspired by Bruno Latour and the "Actor - Network-Theory", where the materiality also has status as an actor, the article argues that the non-humanity has been neglected as an object of analyses of the relations between Norway and Germany. By the material function of the "Folkswagen" and many people’s practical experiences with this car, Norwegians learned Germany to know for new after the Second World War.